On the Issue of Practical Orientation of Teaching Students of Technical Universities the Basics of Descriptive Geometry - L. G. Polyakov; T. D. Polyakova (Открытое образование (Москва))
Purpose of the research. The introduction of a distance education system in the form of an electronic educational environment in modern conditions requires new approaches to increasing the interest of students in learning the material. This is especially true for general education subjects. One of the ways to improve the efficiency of learning disciplines is to link theory with practice. In addition, traditional practical tasks on subjects of the general education cycle do not fully take into account the application of the acquired knowledge in the future professional activity of students. Therefore, the purpose of this work is to study the methodology and develop solutions to tasks that most fully take into account the practical orientation of the studied subjects of the general education cycle in technical universities. Materials and methods. As the object of research, the course of descriptive geometry was chosen as the most difficult subject for students of the first year of higher educational institutions of technical direction. Based on the analysis of the structure of the discipline “descriptive geometry and engineering graphics", the authors propose to link the practical part of the course to a specific technical device. Then, using the accepted assumptions, theoretical positions and goals of studying descriptive geometry, we need to develop a set of interrelated tasks that describe the design of a technical device and the interaction of its elements, allowing you to develop the initial skills of the student with mechanical drawings manually, as well as through computer programs both standard and developed by lecturers of the Department “Descriptive Geometry and Graphics " of the Penza State University of Architecture and Construction. Results. The article presents the results of applying the practical orientation of the theoretical provisions of descriptive geometry for students studying in the direction of “Operation of transport and technological machines and complexes" of the Penza State University of Architecture and Construction. As a visual technical device, the liquid supply regulator, used in automotive equipment is selected. Essentially practical orientation is to solve three interrelated problems to determine controller parameters by the methods of descriptive geometry: relative position of subassemblies of the regulator (integrated positional task); determination of the actual values of the elements of the regulator (how to convert a drawing); characterization of the body of the regulator for creation of the flask when casting (intersection of the surfaces and scan one of the bodies coated with line-crossing). The results of solving the tasks are presented in the form of calculation and graphic works and laid out in the electronic environment of distance learning, as the final report documents for the study of the main sections of the course of descriptive geometry. The lecturer places examples of calculation and graphic works’ implementation in the electronic educational environment, features of formation of initial skills for drawing and reading machine-building drawings, and students upload their decisions to the page of the corresponding course in stages or the work performed as a whole.Conclusion. In the final part of the article, conclusions are formulated based on the results of the research, made by the authors. The conclusions reflect the ways to achieve the goals of studying descriptive geometry using computer technologies and e-education. In addition, the uniqueness and results of using the proposed method in a technical University are shown.